A comparative analysis o the Hague-Visby Rules and the Rotterdam Rules with reference to carrier's liabilitties - Nedjar, Bachir (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
Trade transactions depend primarily on trust and prompt service. It is recognized that the carriage of goods by the sea plays a vital role to promote such features by being the most preferred choice compared to air or railroad transportation. However, the existing law-rules that regulate the international trade could not keep up with these features. The carrier under the Hague-Visby Rules has many opportunities to exempt himself from liability for loss or damage to the cargo in several cases. In addition, the Hague-Visby Rules suffers from the lack of uniformity in the interpretation regarding these exclusionary provisions in different jurisdictions. Such problems have resulted in the carrier's dilution of responsibility, and the fortification of his immunity against the cargo-owner's position. In an attempt to create a fairer balance between the carrier and the cargo interest, UNCITRAL has enacted an alternative legal instrument known as, Rotterdam Rules, to promote the international trade law in general, and to provide global uniformity in the application of the rules to the carriage of goods by sea, in particular with respect to enhancing the carrier's liability. This study compares the application of both rules to the carrier's liability; it elaborates the major obligations of the carrier against the cargo owner. However, it submits that the higher liability of the carriers and ship-owners, led the majority of the powerful industrial countries to ignore the ratification of the Rotterdam Rules and to maintain the application of the Hague/Hague-Visby Rules. In view of these circumstances, this study has revealed an imminent need for ratification the Rotterdam Rules to establish a suitable and effective set of rules to revive maritime law and to promote international trade, particularly, in terms of solving the shipping conflicts between the carriers and the cargo-interests. Finally, the study proposes that all countries should focus their efforts to make necessary improvements to ensure that they are in a position to ratify the Rotterdam Rules in the nearest future for the purpose of establishing international uniformity for multimodal transport.